Salmeterol and Fluticasone Propionate (50/250 μg) Administered via Combination Diskus Inhaler: As Effective as When Given via Separate Diskus Inhalers - Kenneth R Chapman; Nils Ringdal; Vibeke Backer; Mona Palmqvist; Seppo Saarelainen; Mark Briggs (Canadian Respiratory Journal)
OBJECTIVE: To compare the efficacy and safety of a new combination Diskus inhaler containing both salmeterol 50 μg and fluticasone propionate 250 μg (Seretide) with the two drugs delivered via separate Diskus inhalers.